2003
DOI: 10.1109/tac.2003.811264
|View full text |Cite
|
Sign up to set email alerts
|

S-modular games and power control in wireless networks

Abstract: Abstract-This note shows how centralized or distributed power control algorithms in wireless communications can be viewed as S-modular games coupled policy sets (coupling is due to the fact that the set of powers of a mobile that satisfy the signal-to-interference ratio constraints depends on powers used by other mobiles). This sheds a new light on convergence properties of existing synchronous and asynchronous algorithms, and allows us to establish new convergence results of power control algorithms. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 11 publications
(23 reference statements)
1
151
0
1
Order By: Relevance
“…It is shown that through the interaction-learning process, a certain Quality of Service (QoS) can be guaranteed. In (Saraydar, Mandayam & Goodman 2002, Altman & Altman 2003, Huang et al 2006 super-modular games have been used to design various power control algorithms arising in wireless networks. A key feature of super-modular games is strategic complementarity-if a player chooses a higher action, the others want to do the same.…”
Section: 7mentioning
confidence: 99%
“…It is shown that through the interaction-learning process, a certain Quality of Service (QoS) can be guaranteed. In (Saraydar, Mandayam & Goodman 2002, Altman & Altman 2003, Huang et al 2006 super-modular games have been used to design various power control algorithms arising in wireless networks. A key feature of super-modular games is strategic complementarity-if a player chooses a higher action, the others want to do the same.…”
Section: 7mentioning
confidence: 99%
“…Therefore, it is important to address the issue of existence and uniqueness of an equilibrium in a power game. One approach used in [12] to establish the existence of equilibrium in single-input-single-output (SISO) power games is the framework of supermodular games which relies on the monotonicity of best response function. However, this approach is not readily applicable to the MIMO case.…”
Section: A Power Game and Generalized Nash Equilibriummentioning
confidence: 99%
“…is obtained, any link k updates its own covariance matrix according to (12) where 0 ≤ α k (t) ≤ 1 is a parameter that represents the k-th link's willingness to optimize (in other words, 1 − α k (t) is the k-th link's inertia) at step t. The inertia prevents the links from overreacting and generally helps with the convergence of the updates.…”
Section: Best Response Dynamicsmentioning
confidence: 99%
“…Let κ denote the space of all strategies. We present the property of increasing differences (supermodularity) with the following definition [4].…”
Section: ) Learning Theory In Repeated Gamesmentioning
confidence: 99%